Diagnosis and Treatment of Elderly and Senile Chronic Constipation: an Expert Consensus - V. T. Ivashkin; M. G. Mnatsakanyan; V. S. Ostapenko; А. P. Pogromov; V. M. Nekoval; E. A. Poluectova; Yu. V. Kotovskaya; N. K. Runikhina; N. V. Sharashkina; P. V. Tsarkov; N. O. Tkacheva; Yu. N. Belenkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2021)
Aim. An appraisal of practitioners with chronic constipation management details in older and senile adults.Key points. Chronic constipation is a common issue in geriatrics. Aside to age-related physiological bowel disfunction, a higher constipation incidence is conditioned by declined physical activity and frailty, polypharmacy and a series of secondary constipation-developing chronic states and diseases. Chronic constipation is associated with a higher risk of cardiovascular disease and complications, impaired general perception of health and pain, growing alarm and depression, and reduced quality of life. The treatment tactics in chronic constipation is cause-conditioned and should account for the patient’s history and therapy line, overall clinical condition, cognitive status and functional activity level. An essential baseline aspect of constipation management is apprising the patient and his family of the underlying factors and methods for non-drug and drug correction. An higher-fibre diet is recommended as first measure, with osmotic laxatives added and titrated to clinical response if none observed towards the non-drug and high-fibre regimens. Stimulant laxatives and prokinetics should be recommended in patients reluctant to fibre supplements and osmotic laxatives. Subsidiary correction includes biofeedback, transanal irrigation, acupuncture, foot reflexology and percutaneous tibial nerve stimulation.Conclusion. Elderly and senile chronic constipation is a prevalent multifactorial state requiring an efficient management via assessment and correction of total risk factors and consistent use of non-medication and drug therapies.